Patient’s autonomy and decision making in health: acquaintance by Peruvian medical interns - 2010 - Sogi, Cecilia (2012)
Patient’s autonomy and decision making in health: acquaintance by Peruvian medicalinterns - 2010Objectives: To determine acquaintance on patient’s autonomy and decision making in health care in medical interns from five cities of Peru. Design: Opinion poll type study. Setting: Institute of Ethics in Health, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Medical interns. Methods: Five cases from the literature with multiple choice questions were used as the instrument; its validity and reliability was established by both a group of experts and Cronbach alpha. Participants in the study were medical interns from five Peruvian cities: Lima (n=48), Huacho (n=21), Ica (n=24), Trujillo (n=132), and Huancayo (n=47). Main outcome measures: Correct ethical answers. Results: From the interns participating 61,4% were male, mean age 26 (SD 2,8) min 21 and max 47. Correct answers were high in cases 1 (74,3%), 2 (68%) and 5 (62,9%), but its application in the practice were low in cases 1 (7,0%), 2 (3,7%) and 5 (12,5%). Correct answers were low in case 3 (ethical analysis 23,9% and decision 7,7% respectively). In case 4 correct answers were 41,9% and 69,9% respectively. Conclusions: In the context of hypothetical clinical situation, participants' answers suggest good ethical analysis but low application in health decision in three cases; the most frequent answers in these cases suggest defensive medical practice. In addition, knowledge about informed consent in minors was low.